The REIO exception in MFN treatment clauses (UN New YorkUS, 2004)
Examines issues that would assist negotiators of future international investment agreements (IIAs) in assessing the need for a regional economic integration organisation (REIO) exception in IIAs. Seeks to help them to find a proper concept and formulation of the respective clause, where it would be deemed necessary.
Keywords: INVESTMENT